Biological and anti‐vascular activity evaluation of ethoxy‐erianin phosphate as a vascular disrupting agent. Issue 10 (20th May 2019) - Yuan, Wenshuang; Su, Chang; Yang, Xiaotong; Li, Yueqi; Cao, Yiou; Liang, Xin; Liu, Jianwen
Abstract: The effects of ethoxy‐erianin phosphate (EBTP) on cell proliferation, mitotic cell arrest, migration, infiltration, and endothelial tubular structures were evaluated in this study. The antiproliferative activity of EBTP and combretastatin A‐4P (CA4P) was analyzed on several tumor cells (including MCF‐7, HeLa, 2LL, and 2LL‐IDO) and on an endothelial cell (human umbilical vein endothelial cells [HUVECs]) as well as a human normal liver cell (L02). The results showed that EBTP possessed antiproliferative activity in the micromole range and was relatively less toxic than CA4P. Treating HUVECs with EBTP caused cell accumulation in the G2/M phase, and wound‐healing assays indicated that EBTP inhibited cell migration. Furthermore, EBTP and CA4P destroyed the vasculature in endothelial cells and showed vascular disrupting activity of the chorioallantoic membrane in fertilized chicken eggs. In addition, we found that EBTP suppressed the expression of indoleamine 2, 3‐dioxygenase (IDO) and significantly inhibited IDO‐induced migration and infiltration of 2LL‐IDO cells. Administration of EBTP blocked vasculogenic mimicry in 2LL‐IDO cells, which was typically observed in tube formation assays of 2LL‐IDO cells. Moreover, the results of Lewis lung carcinoma in mice showed a high inhibition rate of EBTP. EBTP is an effective vascular disrupting agent that is superior to CA4P and may prevent and treat malignancy by inhibiting the expression of IDO. Abstract : The results of this study indicate that ethoxy‐erianin phosphate (EBTP) has significant antiangiogenic activity in vivo and that it decreases the expression of p‐STAT3 by the inhibition of indoleamine 2, 3‐dioxygenase 1 (IDO1). This study lays the foundation for effectively cutting off blood supply to tumors and provides a direction for cancer treatment.